Perioperative nivolumab monotherapy versus nivolumab plus ipilimumab in resectable hepatocellular carcinoma: a randomised, open-label, phase 2 trial. (March 2022) - Kaseb, Ahmed Omar; Hasanov, Elshad; Cao, Hop Sanderson Tran; Xiao, Lianchun; Vauthey, Jean-Nicolas; Lee, Sunyoung S; Yavuz, Betul Gok; Mohamed, Yehia I; Qayyum, Aliya; Jindal, Sonali; Duan, Fei; Basu, Sreyashi; et al.
Summary: Background: Hepatocellular carcinoma has high recurrence rates after surgery; however, there are no approved standard-of-care neoadjuvant or adjuvant therapies. Immunotherapy has been shown to improve survival in advanced hepatocellular carcinoma; we therefore aimed to evaluate the safety and tolerability of perioperative immunotherapy in resectable hepatocellular carcinoma. Methods: In this single-centre, randomised, open-label, phase 2 trial, patients with resectable hepatocellular carcinoma were randomly assigned (1:1) to receive 240 mg of nivolumab intravenously every 2 weeks (for up to three doses before surgery at 6 weeks) followed in the adjuvant phase by 480 mg of nivolumab intravenously every 4 weeks for 2 years, or 240 mg of nivolumab intravenously every 2 weeks (for up to three doses before surgery) plus one dose of 1 mg/kg of ipilimumab intravenously concurrently with the first preoperative dose of nivolumab, followed in the adjuvant phase by 480 mg of nivolumab intravenously every 4 weeks for up to 2 years plus 1 mg/kg of ipilimumab intravenously every 6 weeks for up to four cycles. Patients were randomly assigned to the treatment groups by use of block randomisation with a random block size. The primary endpoint was the safety and tolerability of nivolumab with or without ipilimumab. Secondary endpoints were the proportion of patients with an overall response, time to progression, and progression-free survival. This trial is registered with ClinicalTrials.gov (NCT03222076 ) and is completed. Findings: Between Oct 30, 2017, and Dec 3, 2019, 30 patients were enrolled and 27 were randomly assigned: 13 to nivolumab and 14 to nivolumab plus ipilimumab. Grade 3–4 adverse events were higher with nivolumab plus ipilimumab (six [43%] of 14 patients) than with nivolumab alone (three [23%] of 13). The most common treatment-related adverse events of any grade were increased alanine aminotransferase (three [23%] of 13 patients on nivolumab vs seven [50%] of 14 patients on nivolumab plus ipilimumab) and increased aspartate aminotransferase (three [23%] vs seven [50%]). No patients in either group had their surgery delayed due to grade 3 or worse adverse events. Seven of 27 patients had surgical cancellations, but none was due to treatment-related adverse events. Estimated median progression-free survival was 9·4 months (95% CI 1·47–not estimable [NE]) with nivolumab and 19·53 months (2·33–NE) with nivolumab plus ipilimumab (hazard ratio [HR] 0·99, 95% CI 0·31–2·54); median time to progression was 9·4 months (95% CI 1·47–NE) in the nivolumab group and 19·53 months (2·33–NE) in the nivolumab plus ipilimumab group (HR 0·89, 95% CI 0·31–2·54). In an exploratory analysis, three (23%) of 13 patients had an overall response with nivolumab monotherapy, versus none with nivolumab plus ipilimumab. Three (33%) of nine patients had a major pathological response (ie, ≥70% necrosis in the resected tumour area) with nivolumab monotherapy compared with three (27%) of 11 with nivolumab plus ipilimumab. Interpretation: Perioperative nivolumab alone and nivolumab plus ipilimumab appears to be safe and feasible in patients with resectable hepatocellular carcinoma. Our findings support further studies of immunotherapy in the perioperative setting in hepatocellular carcinoma. Funding: Bristol Myers Squibb and the US National Institutes of Health.